THE CONTENT OF THE DEVELOPMENT OF A SENSE OF PATRIOTISM IN TEACHERS OF THE FUTURE PHYSICAL CULTURE ON THE BASIS OF A MODERN APPROACH - Fatkhulla Miraxmedov (Proximus Journal Publishing, 2024)
This article was used as an indicator of the assessment of upbringing when introducing the "concept of continuous spiritual education" from the criteria and indicators of the development of civil and Patriotic competence of future teachers. As a result, the ability to diagnose the readiness of future teachers to form students ' loyalty to the Motherland has increased
Keywords: Patriotic consciousness; Patriotic Outlook; moral